Peningkatan Aktivitas Belajar dan Keterampilan Membaca Intensif dengan Melalui Penerapan Metode CIRC dan Media Styrofoam - Sundarini (Nur Science Institute, 2021)
This study aims to improve learning activities and intensive reading skills using the CIRC method and Styrofoam media for class IX F Semester 1 students of SMPN 23 Surakarta in the 2017/2018 academic year. This classroom action research was conducted at SMPN 23 Surakarta in the first semester of the 2017/2018 academic year for 3 months. The research subjects were 30 students of class IX F SMPN 23 Surakarta. The method used in this research is a classroom action research method which is carried out in 2 cycles through 4 stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. In the implementation of classroom action research using observation sheets and learning outcomes tests. Data analysis used comparative descriptive analysis technique. The results showed that the application of the CIRC method and styrofoam media could improve learning activities and intensive reading skills in class IX F Semester 1 of SMPN 23 Surakarta in the 2017/2018 academic year.